Compensatory Strategies Due to Knee Flexion Constraint during Gait of Non-Disabled Adults - Bacca, Odair; Celestino, Melissa Leandro; Barela, José Angelo [UNESP]; Yakovenko, Sergiy; de Lima, Ana Júlia Silva; Barela, Ana Maria Forti (Taylor & Francis, 2021)
Constraining knee flexion of non-disabled individuals could further our understanding regarding the importance of knee joint during gait, which is a common disturbance in individuals with gait impairment. In this study we investigated whether a mechanical constraint of knee flexion in non-disabled adults would lead to compensatory strategies. Eleven non-disabled male adults walked without and with an orthosis that permitted full extension and limited knee flexion up to either 45° or 30°. We analyzed the temporal organization of lower limb kinematics and electromyograms of the rectus femoris, vastus medialis and lateralis, tibialis anterior, semitendinosus, biceps femoris, and gastrocnemius medialis and lateralis. Non-disabled adults compensated for the reduced knee flexion by increasing hip and ankle joint excursions and ankle flexor activation amplitude. Also, these adults shortened pre-swing and lengthened swing duration in the constrained limb and increased the activity of bifunctional hip extensor and knee flexor muscles in the constrained limb in relation to the unconstrained limb. The use of an orthosis that limited knee flexion in non-disabled adults leaded to compensatory strategies in the temporal organization of joint excursions and muscle activations in the constrained limb. The compensatory effects were correlated with the extent of knee flexion constraint.
Keywords: kinematics; locomotion; myography